Avaliação do KIM-1 como biomarcador de lesão tubular renal em pacientes com diabetes mellitus tipo 2 normoalbuminúricos - Oliveira, Laura Eduarda de (2024)
Introduction: Type 2 DM (DMT2) is a complicated, multifactorial disease whose pathogenesis involves decreased insulin production, insulin resistance (IR) and abnormal regulation of glucose production in the liver, leading to the development of alterations in glycemic control and the formation of advanced glycation end products (AGEs). RI in DMT2 is a metabolic alteration that can be assessed using the Homeostasis Model Assessment of Insulin Resistance (HOMA-IR) and is directly linked to the development of microvascular complications resulting from DMT2. Among these complications, diabetes kidney disease is the leading cause of chronic kidney disease and end-stage renal disease. The operational diagnosis of diabetes kidney disease is made using uAlb levels, but studies have already recognized the presence of lesions and altered kidney function in normoalbuminuric patients. Therefore, the kidney injury molecule (KIM-1) has been studied as a potential marker for early assessment of renal tubular alterations, even in normoalbuminuric patients. Objective: To investigate the association of KIM-1 with early tubular damage in normoalbuminuric DMT2 patients and its relationship with insulin resistance assessed by HOMA-IR. Methodology: A cross-sectional study was carried out involving 82 normoalbuminuric DMT2 patients from medical clinic of the University Hospital of Santa Maria (HUSM), who were divided into two groups according to the HOMA-IR using a cut-off point of 2.77 established in a previous study. KIM-1 was determined, along with other biochemical tests. Results: In this study, both groups had uAlb values within the normal range, indicating that these patients would not be diagnosed with diabetes kidney disease using this marker. We found that patients with greater insulin resistance (HOMA-IR > 2.77) had higher KIM-1 values. In addition, these patients had mean KIM1 values of 113.3 mg/g creatinine, above the cut-off point of 109 ng/g creatinine established in a previous study for diagnosing incipient diabetic kidney disease. Conclusion: The main finding of this study was the relationship between patients with higher IR, as assessed by HOMA-IR, and increased urinary KIM-1, even at uAlb values within the normal range. This indicates that KIM-1 could be used for early detection of changes in renal structure resulting from DMT2.